Brain ependymocytes in neurogenesis and maintaining integrity of blood-cerebrospinal fluid barrier - Yu. A. Uspenskaya; A. V. Morgun; E. D. Osipova; S. K. Antonova; A. B. Salmina (Фундаментальная и клиническая медицина)
Here we review the physiology of brain ependymocytes which produce cerebrospinal fluid, regulate neurogenic niches, and contribute to neurogenesis in health and disease. We particularly focus on cilia as these organelles are pivotal to ensure the normal functioning of ependymocytes. The functional activity of ependymocytes is largely defined by their localisation in the central nervous system. Further studies of ependymal cell biology are required to better understand the mechanisms of neurological disorders and to discover novel therapeutic strategies aimed at correcting neurodegeneration and aberrant development of the brain.